Pengaruh Customer Relationship Management (CRM) Terhadap Loyalitas Pelanggan pada Maskapai Penerbangan Garuda Indonesia Melalui Program Frequent Flyer - Eva Dwi Sundari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The aim of this study is to examine the effect of Customer Relationship Management (CRM) on customer loyalty on Garuda Indonesia airlines through frequent flyer programs. The study sample was taken from Garuda Indonesia passengers over the age of 18 years. Primary data was collected through convenience sampling. Regression analysis is used to test hypothese. There is the influence of Customer Relationship Management on Customer Loyalty on Garuda Indonesia airlines, there is a Frequent Flyer influence on customer loyalty on Garuda Indonesia airlines, there is a frequent flyer influence to moderate Customer Relationship Management to Garuda Indonesia Customer Loyalty, there is the effect of Customer Relationship Management, Frequent Flyer for Garuda Indonesia airlines. It is better if further research is conducted in the long term, so that Garuda Indonesia CRM can be explored more far. While Garuda Indonesia's services cover almost all of Indonesia and several other countries. The literature that discusses CRM is still not much so that the dimensions of dimension elaboration are still limited. Research findings reveal the need and importance of a company to continuously improve Customer Relationship Management. This study shows the need to emphasize the use of critical customer loyalty and to recognize the nature and importance of frequent flyer moderation effects. The value of this research is a combined and practical theory and finds four management implications and three practical implications.